An ecological analysis of stink bug and lepidopteran borer complexes associated with pecan and citrus orchards in the Vaalharts region - Van Rooyen, Andre (University of the Free State, 2017)
This study investigates the insect-plant interactions on citrus fruit and pecan nuts in South Africa. The aims of this study were to determine whether lepidopteran borer pests shuttled between adjacent citrus and pecan orchards, and to establish the cultivar preference of the most prevalent stink bug borer species in Vaalharts pecan orchards. Pheromone trap data indicated that there was a significant overlap between the populations of false codling moth (Thaumatotibia leucotreta) and carob moth (Ectomyelois ceratoniae) between adjacent citrus and pecan orchards. Both species of moth were found within the citrus and pecan orchards. Larval eclosions indicated that false codling moths shuttled between adjacent citrus and pecan orchards; however, the direction of the shuttling could not be established. An abundance of citrus fruit drew false codling moths from an adjacent pecan orchard, which increased infestation in the citrus orchard. No significant evidence of carob moth shuttling was found. Adult false codling moths were found to be active throughout the winter, albeit in decreased numbers. Adult carob moths were almost entirely absent during the winter months, although larvae were still present in pecan nuts and citrus fruit. Grey-brown stink bugs (Coenomorpha nervosa) were found to be the most prevalent hemipteran pest on pecan trees in the Vaalharts region. Coenomorpha nervosa demonstrated a significant preference for pecan trees of the Wichita cultivar. Adult and nymph grey-brown stink bugs preferred the Wichita cultivar to Choctaw, Barton, and Navaho cultivars. The investigation could not find C. nervosa exploiting other viable food sources close to pecan orchards; even potential host plants that were not dead or defoliated during winter. Overall, the study indicates that adjacent citrus and pecan orchards will accommodate shuttling of false codling moths between orchards. Furthermore, grey-brown stink bugs were found to be the dominant hemipteran pest on pecan trees the Vaalharts region. Grey-brown stink bugs prefer the Wichita cultivar and do not exploit food sources near pecan trees of the Wichita cultivar.

Hierdie studie het die insek-plant-interaksies op sitrusvrugte en pekanneute in Suid-Afrika ondersoek. Die hoofdoelwitte van hierdie studie was om te bepaal of lepidoptera-boorderpeste tussen aangrensende sitrus- en pekanboorde migreer; asook om die kultivarvoorkeur van die mees algemene stinkbesieboorderspesie in Vaalharts-pekanboorde te bevestig. Feromoonlokvaldata het daarop gedui dat ’n beduidende oorvleueling tussen die bevolkings van valskodlingmot (Thaumatotibia leucotreta) en karobmot (Ectomyelois ceratoniae) tussen aangrensende sitrus- en pekanboorde teenwoordig was. Albei motspesies is gevind in die sitrus- en pekanboorde. Die uitbroei data van larwes het aangedui dat valskodlingmotte tussen aangrensende sitrus- en pekanboorde migreer. Die rigting van die migrasie kon egter nie vasgestel word nie. Oortollige hoeveelhede sitrusvrugte lok valskodlingmotte van ’n aangrensende pekanboord, wat lei tot verhoogde besmetting in die sitrusboord. Geen beduidende bewyse van karobmotmigrasie na aangrensende boorde kon gevind word nie. Daar is gevind dat valskodlingmotvolwassenes aktief is in die winter, maar in verminderde getalle. Karobmotvolwassenes was byna heeltemal afwesig gedurende die wintermaande, alhoewel larwes in beide pekanneute en sitrusvrugte teenwoordig was. Grys-bruin stinkbesies (Coenomorpha nervosa) was die mees algemene besieplaag op pekanbome in die Vaalhartsstreek. ’n Beduidende voorkeur vir pekanbome van die Wichita-kultivar is deur C. nervosa gedemonstreer. Beide volwasse en nimf grys-bruin stinkbesies verkies die Wichita-kultivar bo Choctaw-, Barton-, en Navaho-kultivars. Dit kon nie bewys word dat C. nervosa voedselbronne naby pekanboorde gebruik nie, selfs potensiële gasheerplante wat nie in die winter ontbos of vrek nie. Die studie het getoon dat aangrensende sitrus- en pekanboorde migrasie van valskodlingmotte tussen boorde sal akkommodeer. Voorts is gevind dat grys-bruin stinkbesies die dominante besieplaag op pekanbome in die Vaalhartsstreek is. Grys-bruin stinkbesies toon ’n voorkeur vir die Wichita-kultivar en maak nie gebruik van voedselbronne naby pekanbome van die Wichita-kultivar nie.
Dissertation (M.Sc. ((Zoology and Entomology))--University of the Free State, 2017
Keywords: Lepidopteran borer shuttling; Species overlap; False codling moth; Carob moth; Grey-brown stink bug; Host preference; Wichita cultivar; Thaumatotibia leucotreta; Ectomyelois ceratoniae; Coenomorpha nervosa; Lepidoptera; Insects; Pecan -- Diseases and pests -- South Africa -- Vaalharts; Fruit trees -- Diseases and pests -- South Africa -- Vaalharts